2018
DOI: 10.14202/vetworld.2018.557-561
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of a partial CDS of leptospiral ligA gene in pET-32a - Escherichia coli DH5α system

Abstract: AimThis study aims at cloning, sequencing, and phylogenetic analysis of a partial CDS of ligA gene in pET-32a - Escherichia coli DH5α system, with the objective of identifying the conserved nature of the ligA gene in the genus Leptospira.Materials and MethodsA partial CDS (nucleotide 1873 to nucleotide 3363) of the ligA gene was amplified from genomic DNA of Leptospira interrogans serovar Canicola by polymerase chain reaction (PCR). The PCR-amplified DNA was cloned into pET-32a vector and transformed into comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Target genes inserted in pET plasmids are under the control of the T7 promoter and expression is induced by providing T7 RNA polymerase in the host cell. T7 RNA polymerase has a high degree of selectivity and activity, which helps to locate almost all cellular resources on the expression of specific genes [29]. Our research found that the pET-32a (+) vector tended to facilitate the efficient expression of RIPK3 protein relative to other vectors.…”
Section: Discussionmentioning
confidence: 76%
“…Target genes inserted in pET plasmids are under the control of the T7 promoter and expression is induced by providing T7 RNA polymerase in the host cell. T7 RNA polymerase has a high degree of selectivity and activity, which helps to locate almost all cellular resources on the expression of specific genes [29]. Our research found that the pET-32a (+) vector tended to facilitate the efficient expression of RIPK3 protein relative to other vectors.…”
Section: Discussionmentioning
confidence: 76%